2009
DOI: 10.1007/978-3-642-04244-7_61
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Based Local Search for the Automatic Generation of Architectural Tests

Abstract: Abstract. This paper considers the automatic generation of architectural tests (ATGP), a fundamental problem in processor validation. ATGPs are complex conditional constraint satisfaction problems which typically feature both hard and soft constraints and very large domains (e.g., all memory addresses). Moreover, the goal is to generate a large number of diverse solutions under tight runtime constraints. To improve solution diversity, this paper proposes a novel approach to ATGPs by modeling them as MaxDiverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…A number of other studies (Petit and Trapp 2015, Trapp and Konrad 2015, Camm 2014, Eiter et al 2013, Hebrard et al 2011, Danna and Woodruff 2009, Schittekat and Sörensen 2009, Hentenryck et al 2009a, Glover et al 2000, Kuo et al 1993 have demonstrated interest in exploration beyond the single solution returned by the solver. These studies discuss generating multiple solutions to combinatorial problems, and some further integrate diversity into their discussions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies (Petit and Trapp 2015, Trapp and Konrad 2015, Camm 2014, Eiter et al 2013, Hebrard et al 2011, Danna and Woodruff 2009, Schittekat and Sörensen 2009, Hentenryck et al 2009a, Glover et al 2000, Kuo et al 1993 have demonstrated interest in exploration beyond the single solution returned by the solver. These studies discuss generating multiple solutions to combinatorial problems, and some further integrate diversity into their discussions.…”
Section: Introductionmentioning
confidence: 99%
“…Problems instances were generated using the graph generator programs written by Joseph Culberson 4 with parameter values p = 0.5, k ∈ [3,10], n ∈ {25, 50, 75, 100} and 5 instances per setting. 5 The problem model uses a not-equal constraint for each pair of adjacent vertexes. It uses max/min search.…”
Section: Methodsmentioning
confidence: 99%
“…Constraint-based local search (CBLS) has been quite successful in solving problems that prove difficult for constraint solvers based on constructive search. Unfortunately, there is little published work on existing implementations that led to this success -most work has addressed language features [12,7,8] and applications [5,2]. In this paper we present Kangaroo, a new constraint-based local search system and expose key details of its implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first approaches to this problem relied on heuristic methods (Hebrard et al, 2005;Hentenryck, Coffrin, & Gutkovich, 2009), It was also shown that when the problem P allows it, knowledge compilation methods could efficiently solve this problem (Hadzic, Holland, & O'Sullivan, 2009). …”
Section: Constraint Formulationmentioning
confidence: 99%